Sixth Review of the Fund's Data Standards Initiatives : Metadata Standardization in the Data Quality Program. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Supplement describes how the staff proposes to achieve further synergies by mapping the DQAF into the metadata structure of the DQP's other key component: (3) the data transparency initiatives comprising the Special Data Dissemination Standard (SDDS) and General Data Dissemination System (GDDS).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: GDDS Metadata Element; GDDS Metadata Model; Information; PP; SDMX